(untitled) (Transport systems and technologies, 2022)
Promising electromotive rolling stock is based on application of asynchronous traction engines with a short-circuited rotor. The use of asynchronous traction motor controller allows: increase power, tractive force and speed of electromotive rolling stock, promote reliability and bring down the cost of life cycle, increase lifetime. In addition to this asynchronous traction motor controller of double power gives an opportunity to provide train traffic through the areas of direct current with a voltage of 3 kV as well as on the areas of alternating current with voltage of 25 kV at a frequency of 50 Hz without replacement of electromotive rolling stock. In the article the mathematical model of asynchronous traction engine is considered taking into account electric and mechanical part of traction motor controller. A model describes electromagnetic processes in stator windings in the fixed α, β, γ coordinate system, which has its axis combined with the axis of stator phases A, B, C. Processes in a shortcircuited rotor are described in the rotating a, b, c coordinate system. For the modeling of mechanical part of motor controller basic equation of dynamics, that characterizes ratio between an electromagnetic torque and section modulus in the shaft of the electric motor, is used. In a proposed model simulation and structural modeling methods were implemented by means of function modules of the Simulink library. A model allows to investigate transition processes given: nonsinusoidal and asymmetric supply voltage; saturation of the magnetic system; current crowding out effect in the rotor conductors; presences of shortings between the turns of the stator winding and damages of rotor rods. A mathematical model is implemented as matrix Simulink model of asynchronous engine in MatLab. Credibility of the mathematical model was checked up while conducting virtual researches of electromechanics characteristics of asynchronous engine of type AD914.The outcome confirmed the adequacy of the implemented model and the possibility of the implemented model to be used in other applications.